Case Report: Pathological Complete Response in a Brain-Metastatic Lung Squamous Cell Carcinoma Patient With Long-Term Benefit From Chemo-Immunotherapy - Hu, Chen; Ma, Qiang; Li, Nengsheng; Luo, Nuo; Hao, Shuai; Jiang, Minrui; Pang, Fei; Yang, Yan; Li, Li; He, Yong (Frontiers in Oncology, 2021)
Immune checkpoint inhibitors have already become one of the standard treatment options for advanced non-small cell lung cancer patients without driver gene mutations. However the reasons why some patients still have long-term survival benefits even after immunotherapy withdrawal are still not completely clear. The result of NADIM trial indicated that locally advanced lung cancer patients benefit from neoadjuvant immunotherapy, supported by the high proportion of tumors that achieved a pathological complete response. Here we report, for the first time, a case of an advanced lung squamous-cell carcinoma patient with brain metastasis who received surgical treatment after immunotherapy and was finally radically cured, in order to better clarify the role of immunotherapy on the treatment of non-small cell lung cancer.